The role of hydrogen sulphide in blood pressure regulation - Cacanyiova, S; Berenyiova, A; Kristek, F (Physiological research, 2016)
Cardiovascular studies have confirmed that hydrogen sulphide (H(2)S) is involved in various signaling pathways in both physiological and pathological conditions, including hypertension. In contrast to nitric oxide (NO), which has a clear vasorelaxant action, H(2)S has both vasorelaxing and vasoconstricting effects on the cardiovascular system. H(2)S is an important antihypertensive agent, and the reduced production of H(2)S and the alterations in its functions are involved in the initiation of spontaneous hypertension. Moreover, cross-talk between H(2)S and NO has been reported. NO-H(2)S interactions include reactions between the molecules themselves, and each has been shown to regulate the endogenous production of the other. In addition, NO and H(2)S can interact to form a nitrosothiol/s complex, which has original properties and represents a novel nitroso-sulphide signaling pathway. Furthermore, recent results have shown that the interaction between H(2)S and NO could be involved in the endothelium-regulated compensatory mechanisms that are observed in juvenile spontaneously hypertensive rats. The present review is devoted to role of H(2)S in vascular tone regulation. We primarily focus on the mechanisms of H(2)S-NO interactions and on the role of H(2)S in blood pressure regulation in normotensive and spontaneously hypertensive rats.
Keywords: Gasotransmitters; vazodilatace; gasotransmitery; vazomotorický systém; Vasodilation; Hypertension; oxid dusnatý; svaly hladké cévní; krysa rodu Rattus; zvířata; Nitric Oxide; Vasomotor System; vazokonstrikce; Hydrogen Sulfide; krevní tlak; potkani inbrední SHR; hypertenze; buněčný převod mechanických signálů; sulfan; Rats; Animals; Mechanotransduction, Cellular; Muscle, Smooth, Vascular; Vasoconstriction; Blood Pressure; Rats, Inbred SHR